A SOA and DBUS-based Robotic Component Interaction (Journal of Scientific Research, 2023)
Rewriting and executing codes violate the SOLID principle of object-oriented programming. Robotics being an emerging platform, it becomes hard to write the code from scratch. We focus on using what is already built in as a Robotics Component instead of writing something from scratch. The intention is to minimize development effort and produce the desired result on time without rewriting the software components. By allowing functionalities of different components to be brought into a single component, we are saving the time required for code conversion or replication of functionality written in one language to another. So an architecture with these properties seems ideal for integrating different components. Integration is one of the most fundamental problems in designing autonomous mobile robots, especially those interacting with people in real-life settings. This paper presents an approach to building complex systems from different robotics packages available as open source components (PLAYER, STAGE, GAZEBO, CARMEN). DBUS is a message-oriented protocol for communicating among processes running on the same desktop. SOA provides access to the services over the network and adds novelty to our application.